EFEITOS DAS MUDANÇAS CLIMÁTICAS SOBRE A DISTRIBUIÇÃO DE PIARACTUS MESOPOTAMICUS (CHARACIFORMES, SERRASALMIDAE) NA BACIA DOS RIOS PARANÁ-PARAGUAI - Menezes, Amanda; Da Silva, Valéria; Bailly, Dayani; Cassemiro, Fernanda (ANAIS DO ENIC, 2018)
-